Social Trust, Religiosity, and Self-Rated Health in the Context of National Religious Pluralism - Upenieks, Laura (Journal of religion and health, 2022)
Trust and religiosity have been individually linked to better health outcomes, but little existing research examines how they may combine to shape health. Drawing on data from the 6th and most recent wave of the World Values Survey, we examine the relationship between particularized and generalized social trust, two dimensions of religiosity (religious attendance and one’s belief in the importance of God), and self-rated health across 27 countries. Findings from multilevel models suggest that trust tends to be higher in more religiously pluralistic national contexts, while religiosity in these contexts helps individuals maintain good health. In particular, a higher importance of God (but not religious attendance) can offset the negative health effects of holding low trust in strangers and non-family members (generalized trust), but only in highly pluralistic national contexts. We conclude by offering future research directives that may shed light on the cultural complexities of the various national contexts and their religious compositions.